PSGL-1 is a novel tumor microenvironment prognostic biomarker with cervical high-grade squamous lesions and more - Lin, Yingying; Huang, Shan; Qi, Yuanjie; Xie, Li; Jiang, Junying; Li, Hua; Chen, Zhiwei (Frontiers in Oncology, 2023)
Background Macrophages secrete many cytokines and chemokines, which can provoke either an anti-tumor or pro-tumor immune response. P-selectin glycoprotein ligand-1 (PSGL-1) is expressed in macrophages and plays a vital role in synergizing for a more robust anti-tumor response. However, there are few studies about PSGL-1 expression status and clinical value of biological function in cervical cancer. Methods In this study, 565 participants were enrolled. PSGL-1 mRNA was detected by real-time quantitative PCR (qPCR) with cervical cytology specimens. The relationship between PSGL-1 and cervical intraepithelial neoplasia in two grades and more (CIN2+) was analyzed, and the optimal cut-off values of PSGL-1 to predict CIN2+ were calculated. In addition, the clinical significance of PSGL-1 in cervical cancer was determined by Kaplan-Meier Cox regression based on the database. Results The mean PSGL-1 increased significantly with cervical lesion development, especially compared with CIN2+ (p<0.05). Moreover, the expression of PSGL-1 increased significantly in HPV-16/18 positive and HPV-18 positive, but not in HPV-16 positive and other HR-HPV positive. And then, it demonstrated that the area under the receiver operating characteristic curve (AUC) of PSGL-1 was 0.820, and an optimal cut-off 0.245. Furthermore, the PSGL-1 had the highest odds ratio and highest OR (OR= 8.707; 95% CI (.371-19.321)) for the detection of CIN 2+. In addition, our result also indicated that higher PSGL-1 expression was significantly related to a better prognosis in cervical cancer due to immune cell infiltration. Conclusions PSGL-1≥0.245 in cervical cytology specimens is a new auxiliary biomarker of CIN2+, and it may be a promising prognosis predictor and potential immunotherapy target linked with immune infiltration of cervical cancer.